2011
DOI: 10.1128/aem.02498-10
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Solvent Tolerance Analysis ofPseudomonassp. Strain VLB120ΔC Catalytic Biofilms

Abstract: Biofilms are ubiquitous surface-associated microbial communities embedded in an extracellular polymeric (EPS) matrix, which gives the biofilm structural integrity and strength. It is often reported that biofilm-grown cells exhibit enhanced tolerance toward adverse environmental stress conditions, and thus there has been a growing interest in recent years to use biofilms for biotechnological applications. We present a time-and locus-resolved, noninvasive, quantitative approach to study biofilm development and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…During this time period, a flat biofilm was developed (Figure 1), which fully adapted to the fluidic and hydrophobic stresses and recovered its structure ( Figure 1J). Our previous findings revealed that addition of solvents such as styrene stimulates and increases the EPS production in biofilms [16]. Similar findings of alteration and enhancement of EPS production was observed after chromium exposure in membrane cultivated Pseudomonas putida biofilms [17].…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…During this time period, a flat biofilm was developed (Figure 1), which fully adapted to the fluidic and hydrophobic stresses and recovered its structure ( Figure 1J). Our previous findings revealed that addition of solvents such as styrene stimulates and increases the EPS production in biofilms [16]. Similar findings of alteration and enhancement of EPS production was observed after chromium exposure in membrane cultivated Pseudomonas putida biofilms [17].…”
Section: Resultssupporting
confidence: 64%
“…Cells in the biofilm experienced severe membrane damage upon styrene exposure through the silicone membrane but were able to adapt to the solvent over 48 h in minimal medium containing glucose as sole carbon and energy source [16]. This work here focuses on understanding the cellular response, growth, and biocatalytic performance when exposed to a pure styrene environment in a continuous-flow capillary microreactor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations